KAJIAN YURIDIS TENTANG PELAKSANAAN ITSBAT NIKAH MENURUT HUKUM POSITIF INDONESIA DI KABUPATEN BANTUL - Sri Suwarni; Sri Hendarto Kunto Hermawan (Universitas Janabadra, 2017)
The purpose of this study was to find out the reasons for the petition (itsbat) of marriage and the constraints faced in the implementation of itsbat marriage in Bantul regency. This research is done by research method in the form of library research and also conducted field research. In library research, this research used document study to get secondary data,furthermore,field research was done to obtain primary data within qualitative approach that was by conducting interview. Data, which was obtained from the results of literature research and field research,were analyzed qualitatively. The data were further elaborated with descriptive method of analysis, i.e. in discussing the problem was by identifying, analyzing and interpreting data that has been obtained to be taken a conclusion.The result of this research is that the most important reason for the itsbat of marriage in the Religious Court of Bantul Regency is because married couples who have been married but have not or do not have authentic evidence of marriage events that have been done in the form of Marriage Certificate or Marriage Letter. The marriage petition filed is in conformity with the provisions of Article 7 paragraph (2) of the Compilation of Islamic Law which stipulates that in the case of marriage cannot be proven by the Marriage Deed, it can be filed itsbat marriage to the Religious Court. And the petition of marriage that has been granted by the Panel of Judges handling the petition of marriage in the Religious Court of Bantul is also in accordance with the provisions of Article 7 paragraph (3) letter d and letter e, namely the existence of marriage that occurred before the enactment of Law Number 1 Year 1974, and marriages committed by those who do not have marital obstacles according to Law No. 1 of 1974. And the obstacles faced in the implementation of itsbat marriage in Bantul Regency is, most closely related to the proof of the witness who must be presented in the trial, most of those who witnessed marriage had died. Other constraints, especially rural communities, because of the cost factor they have to pay to apply, although actually for the application for people who can afford this is not a problem, while others are still many people who do not understand the existence of assistance for the discharge of the cost of the case who are indigent.Keywords: Implementation, Itsbat Marriage, Positive Law.